PERILAKU GAYA HIDUP GENERASI MUDA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN - febi, febi; Susilo, Joko Hadi; Wuryaningsih; Kholilurrohman, M. (Jurnal Investasi Islam, 2019)
This study aims to examine the inï¬‚ uence of the lifestyle of the younger generation and the quality of service provided by the coffee shop on the decision of the young generation to visit (buy) products at a coffee shop. The research method used was a survey method. The sampling technique used was porposive sampling, while the number of samples used in this study was 85. The results of this study indicate that the lifestyle of the younger generation and the quality of coffee shop services have a signiï¬ cant effect on purchasing decisions for young generation products in coffee shops. In addition, this study also has empirical and practical implications, that the lifestyle of consumers (young generation) and service quality are important factors to be considered by both coffee shop entrepreneurs and researchers.